PELAKSANAAN PROGRAM PERKESMAS DI PUSKESMAS KOTA BENGKULU - Hermansyah, Hermansyah; Ratna Dewi, Agung Riyadi, (JURNAL MEDIA KESEHATAN, 2017)
Public Health Care activities in Bengkulu city were only well implemented in Ratu Agung Public Health Center, Padang Serai Public Health Center, Beringin Raya Public Health Center, and Betungan Public Health Center. Public Health Center is regularly sent statements. There are 8751 households vulnerable in the city of Bengkulu, and 500 families who have fostered (5.71%). The purpose of this research was to determine the factors associated with the implementation of public health care in Bengkulu City. The type of this research was analytic cross-sectional design. The research population were public health care’s nurse managers in 20 public health centers in Bengkulu city, amounting 24 people. Samples were taken with a total sampling technique. Data were collected by using questionnaires and observation guidelines. The data were analyzed using univariate, bivariate analysis using Pearson product moment correlation test and chi-square. The results showed that almost half (45.8%) of respondents stated public health care implementation in public health centers were less category. The bivariate analysis showed that the independent variables associated with the implementation of public health center activities in Bengkulu city were variables of planning (p = 0.025) and control variables (p = 0.014), whereas the variables of training, knowledge, attitude, skill, organization, and mobilization/implementation were not connected. To improve the implementation of public health care activities in public health centers in Bengkulu city, Health Office should requires all public health center leaders implementing the good planning functions and control the human resource of nurse managers.